The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0100-879x2000001100018
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of NK-1 receptors in the lateral commissural nucleus tractus solitarii of awake rats had no effect on the cardiovascular responses to chemoreflex activation

Abstract: The neurotransmission of the chemoreflex in the nucleus tractus solitarii (NTS), particularly of the sympatho-excitatory component, is not completely understood. There is evidence that substance P may play a role in the neurotransmission of the chemoreflex in the NTS. Microinjection of substance P (50 pmol/50 nl, N = 12, and 5 nmol/50 nl, N = 8) into the commissural NTS of unanesthetized rats produced a significant increase in mean arterial pressure (101 ± 1 vs 108 ± 2 and 107 ± 3 vs 115 ± 4 mmHg, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Lower doses of SP (0.001 and 0.01 nmol/100 nl) had no cardiovascular effects. The pressor/tachycardic effect of a dose close to the ED 50 was blocked by previous injection of a NK-1 antagonist as reported previously (44). Most studies in anesthetized animals using low doses of SP (0.00007-0.06 nmol) have reported short lasting hypotension (4, Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Lower doses of SP (0.001 and 0.01 nmol/100 nl) had no cardiovascular effects. The pressor/tachycardic effect of a dose close to the ED 50 was blocked by previous injection of a NK-1 antagonist as reported previously (44). Most studies in anesthetized animals using low doses of SP (0.00007-0.06 nmol) have reported short lasting hypotension (4, Fig.…”
Section: Discussionsupporting
confidence: 78%
“…The transmitter within these NK 1 -containing neurons may include glutamate, since (1) microinjection of SP in the cNTS results in blood pressure elevation (Zhang et al, 2000), and (2) increased blood pressure may result from activation of NTS glutamatergic neurons projecting to sympathoexcitatory neurons in the rostral ventrolateral medulla (RVLM; (Mazzone et al, 1997; Mauad and Machado, 1998; Babic and Ciriello, 2004; Bailey et al, 2004). However, the SP-induced elevation in blood pressure is not blocked by bilateral microinjection of an NK 1 receptor antagonist in the lateral cNTS (Zhang et al, 2000), suggesting a lack of direct involvement of these receptors in mediating chemoreflexes. In contrast, NK 1 receptors in the NTS are highly implicated in bronchopulmonary reflexes that defend the lungs against injury from inhaled agents by the induction of apnea, cough, and hypotension (Mutoh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The excitatory transmitters in these sensory vagal inputs include glutamate and substance P (SP; Helke et al, 1980; Douglas et al, 1982; Kalia et al, 1984; Kawano and Chiba, 1984; Kawano and Masuko, 1997; Kawano and Masuko, 1995; Lindefors et al, 1986; Srinivasan et al, 1991), a tachykinin peptide that preferentially acts through G protein coupled neurokinin-1 (NK 1 ) receptors (Rodier et al, 2001; Rico et al, 2003; Bonham et al, 2004). Moreover, brainstem SP-induced activation of NK 1 receptors can modulate cardiovascular and respiratory responses evoked through the respective baro- and chemoreceptor reflexes (Gillis et al, 1980; Lindefors et al, 1986; Hall et al, 1989; Massari et al, 1998; Zhang et al, 2000; Nattie and Li, 2002). These observations are consistent with the electron microscopic autoradiographic localization of NK 1 receptor binding sites to postsynaptic neurons in the NTS (Jia et al, 1996; Baude and Shigemoto, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Of the numerous neurotransmitters found in the NTS, glutamate is the principal excitatory neurotransmitter and has been recognized to play a pivotal role in regulating cardiovascular functions in the NTS (Seagard et al, 2001;Talman et al, 1980;Talman, 1997). Studies have also suggested that substance P (SP), acting at neurokinin-1 (NK1) receptors (Feldman, 1995;Zhang et al, 2000), plays a role in neuromodulation of cardiovascular control in the NTS (Boscan et al, 2002;Gillis et al, 1980;Potts, 2006), though a role for the peptide in transmission of baroreflex signals has been controversial. For example, administration into the NTS of SP or agonists for NK1 receptors evoked contradictory arterial baroreceptor responses (Bauman et al, 2002;Carter and Lightman, 1985;Feldman, 1995;Kubo and Kihara, 1987;Nagashima et al, 1989;Talman and Reis, 1981).…”
Section: Introductionmentioning
confidence: 99%